PERLINDUNGAN HUKUM TERHADAP ISTRI MENURUT UNDANG UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Johan Johan (Valid: Jurnal Ilmiah, 2016)
Violence can occur within the scope of household members as a whole, not just violent husband on the wife. However, data obtained from both the research and case reports from various institutions that care for women, shows that the majority of cases of domestic violence is the husband of the wife. "Domestic Violence is any action against someone, especially women, misery or suffering physical, sexual, psychological, and/or negligence of household including a threat to commit acts, coercion, or deprivation of liberty unlawfully within the scope of household, The aim of this research 1). To know the form perlindungaan laws against criminal liability for the wife and husband were involved in perpetrators of domestic violence. 2). To know the efforts to be made by the government in preventing domestic violence. The method used in this research is the method of juridical empirical research which is basically to first see the applicable legal norms subsequently seen how its implementation in the field, whether or not in accordance with the provisions and the underlying theories. The results of this study concluded that 1) the form of legal protection against the wife physically and psychologically as a victim of domestic violence, among others, have been determined in the law on Domestic Violence (domestic violence). 2). Bentuk Domestic Violence (domestic violence) in the form of physical and psychological violence, sexual violence, economic violence. Cases of domestic violence committed by a husband against his wife is to a complaint not offence unusual in the sense that cases of domestic violence whose victims are the wife and the culprit is the new husband is processed criminally if there is a complaint of wives as the victim to the police by themselves or give power to others